2006
DOI: 10.2337/diacare.29.04.06.dc05-1723
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the Protein Kinase C-β Gene (PRKCB1) Accelerate Kidney Disease in Type 2 Diabetes Without Overt Proteinuria

Abstract: OBJECTIVE -We investigated the contribution of PKC-␤ gene (PRKCB1) polymorphisms to diabetic kidney disease in a prospective observational follow-up study.RESEARCH DESIGN AND METHODS -A total of 364 Japanese subjects with type 2 diabetes without overt proteinuria were enrolled during 1996 -1998 and followed until 2004. Five single nucleotide polymorphisms (Ϫ1504C/T, Ϫ546C/G, Ϫ348A/G, Ϫ278C/T, and Ϫ238C/G) in the promoter region of PRKCB1 were genotyped. The end points were transition from stage to stage of dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 21 publications
0
20
1
Order By: Relevance
“…Interestingly, genetic susceptibility might play a role in the development of normoalbuminuric renal insufficiency. It has been reported that polymorphisms of the protein kinase C-β gene (PRKCB1) were associated with diabetic nephropathy that did not lead to albuminuria in Japanese patients (28). …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, genetic susceptibility might play a role in the development of normoalbuminuric renal insufficiency. It has been reported that polymorphisms of the protein kinase C-β gene (PRKCB1) were associated with diabetic nephropathy that did not lead to albuminuria in Japanese patients (28). …”
Section: Discussionmentioning
confidence: 99%
“…Also, SNPs with r 2 Ն 0.80 are considered redundant because 80% of their information overlaps, so selecting just 1 of them would be more cost-effective. In addition, we selected 6 SNPs (rs3760106, rs2575390, rs3900007, rs3900008, rs432998, and rs3729904) with suggestive evidence of association from previous studies, 23,24 so a total of 18 SNPs were genotyped in all study participants in 2009 using genomic DNA.…”
Section: Protein Kinase C-〉 1 Gene and End-stage Renal Diseasementioning
confidence: 99%
“…Patients with type 1 diabetes carrying 2 single-nucleotide polymorphisms (SNPs) in the promoter region of PRKCB1 had increased risk of nephropathy, 23 while Japanese patients with type 2 diabetes carrying these variants had increased risk of deterioration in renal function. 24 Given the increasing recognition of interethnic differences in both distribution and frequency of SNPs for the same gene, 1,25 as well as the high risk for DKD in the Chinese population, 26 we used the HapMap database specific to the Han Chinese population (CHB) to examine the gene structure in Chinese individuals and examined whether polymorphisms in PRKCB1 are associated with risk of new-onset ESRD in a large prospective cohort of Chinese patients with type 2 diabetes.…”
mentioning
confidence: 99%
“…Subjects and examination A total of 249 Japanese type 2 diabetic patients without overt proteinuria were recruited from individuals who regularly visited the outpatient clinic of the Department of Medicine at Shiga University of Medical Science during 1996-1998, as reported previously [13]. Briefly, in the initial 2 years (baseline period) patients clinically diagnosed as having type 2 diabetes according to the WHO criteria [14] provided multiple 24-h urine samples for assessment of urinary AER and eGFR.…”
Section: Methodsmentioning
confidence: 99%